Reclaiming the state: a progressive vision of sovereignty for a post-neoliberal world - Mitchell, William; Fazi, Thomas (London, 2017)
"The crisis of the neoliberal order has resuscitated a political idea widely believed to be consigned to the dustbin of history. Brexit, the election of Donald Trump, and the neo-nationalist, anti-globalisation and anti-establishment backlash engulfing the West all involve a yearning for a relic of the past: national sovereignty. In response to these challenging times, economist William Mitchell and political theorist Thomas Fazi reconceptualise the nation state as a vehicle for progressive change. They show how despite the ravages of neoliberalism, the state still contains resources for democratic control of a nation's economy and finances. The populist turn provides an opening to develop an ambitious but feasible left political strategy. Reclaiming the State offers an urgent, provocative and prescient political analysis of our current predicament, and lays out a comprehensive strategy for revitalising progressive economics in the 21st century."